Vanadium oxide metal-insulator phase transition in different types of one-dimensional photonic microcavities - Scotognella, Francesco (Frontiers in Photonics, 2023)
The optical properties of vanadium dioxide (VO2) can be tuned via metal-insulator transition. In this work, different types of one-dimensional photonic structure-based microcavities that embed vanadium dioxide have been studied in the spectral range between 900 nm and 2000 nm. In particular, VO2 has been sandwiched between: i) two photonic crystals made of SiO2 and ZrO2; ii) two aperiodic structures made of SiO2 and ZrO2 that follow the Thue-Morse sequence; iii) two disordered photonic structures, made of SiO2 and ZrO2 in which the disorder is introduced either by a random sequence of the two materials or by a random variation of the thicknesses of the layers; iv) two four material-based photonic crystals made of SiO2, Al2O3, Y2O3, and ZrO2. The ordered structures i and iv show, respectively, one and two intense transmission valleys with defect modes, while the aperiodic and disordered structures ii and iii show a manifold of transmission valleys due to their complex layered configurations. The metal-insulator transition of VO2, controlled by temperature, results in a modulation of the optical properties of the microcavities.